Modeling in Competitive Activities and Training of Athletes Based on Individual Characteristics (Intersections of Faith and Culture: American Journal of Religious and Cultural Studies (2993-2599), 2025)
This article discusses modeling in competitive activities and the training of athletes based on their individual characteristics. Additionally, it addresses generalized and grouped model systems in the training process.